2017
DOI: 10.1038/s41598-017-14628-x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Mutation Rate has an Exponential Dependence on Population Size for Eukaryotic-length Genomes with Crossover

Abstract: The critical mutation rate (CMR) determines the shift between survival-of-the-fittest and survival of individuals with greater mutational robustness (“flattest”). We identify an inverse relationship between CMR and sequence length in an in silico system with a two-peak fitness landscape; CMR decreases to no more than five orders of magnitude above estimates of eukaryotic per base mutation rate. We confirm the CMR reduces exponentially at low population sizes, irrespective of peak radius and distance, and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Random mutations occur at a rate of µ = 9.1528 × 10 − 6 per locus per generation. This mutation rate is based on the average mutation rates observed in A. thaliana and adjusted to per-locus rates by multiplying it with the average length of a eukaryotic gene (1346bp) (Aston et al . 2017; Xu et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Random mutations occur at a rate of µ = 9.1528 × 10 − 6 per locus per generation. This mutation rate is based on the average mutation rates observed in A. thaliana and adjusted to per-locus rates by multiplying it with the average length of a eukaryotic gene (1346bp) (Aston et al . 2017; Xu et al .…”
Section: Methodsmentioning
confidence: 99%
“…Mutations were randomly and uniformly sampled across the n l loci at a rate of µ = 9.1528 × 10 −6 per locus per generation. This mutation rate is based on the average mutation rates observed in Arabidopsis thaliana and adjusted to per-locus rates by multiplying it with the average length of a eukaryotic gene (1346bp) (Aston et al 2017;Xu et al 2006). A. thaliana was chosen as it is a model plant species with good estimates of mutation rates.…”
Section: Slim Implementationmentioning
confidence: 99%
“…If the explorer chromosomes are defined as having a higher mutation probability than the conservative chromosomes, the optimal solution can be obtained [6]. Several researchers have set the probability as 1/l for the mutation operator, where l is the chromosome length [43,45,46]. Accordingly, mutation probabilities of 1/l and 0.75 (default) were used for the conservative and the explorer chromosomes, respectively, in this study.…”
Section: Test Generation Toolmentioning
confidence: 99%
“…The default of the mutation probabilities in EvoSuite is 0.75. Several researchers [18,50] demonstrated that 1/l is an efficient mutation probability, where l is the length of chromosomes. Therefore, the mutation probability of conservative chromosomes was defined as 1/l and that of explorer chromosomes was assigned the default value (0.75) because 1/l has a smaller value than the default value.…”
Section: Parameter Tuningmentioning
confidence: 99%